The Compliance of Prescribed Activity Restriction in Women at High Risk for Preterm Birth - Bitar, Ghamar; Sciscione, Anthony (American Journal of Perinatology, 2020)
Objective Despite lack of evidence to support efficacy, activity restriction is one of the most commonly prescribed interventions used for the prevention of preterm birth. We have a departmental policy against the use of activity restriction but many practitioners still prescribe it in an effort to prevent preterm birth. We sought to evaluate the rate and compliance of women who are prescribed activity restriction during pregnancy to prevent preterm birth.Study Design This was a single-site retrospective questionnaire study at a tertiary care, academic affiliated medical center. Women with a history of preterm delivery or short cervix were included. Once patients were identified, each patient was contacted and administered a questionnaire. We assessed the rates of activity restriction prescription and compliance. Secondary outcomes included details regarding activity restriction and treatment in pregnancy. Continuous variables were compared with t-test and categorical variables with Chi-square test. The value p < 0.05 was considered significant.Results Among the 52 women who responded to the questionnaire, 18 reported being placed on activity restriction by a physician, with 1 self-prescribing activity restriction, giving a rate of our primary outcome of 19 of 52 (36.5%). All women reported compliance with prescribed activity restriction (100%). Gestational age at delivery was not different in women placed on activity restriction.Conclusion This questionnaire suggests that approximately one in three high-risk women were placed on activity restriction during their pregnancy despite a departmental policy against its use. The 100% compliance rate in patients placed on activity restriction is a strong reminder of the impact prescribing patterns of physicians can have on patients.Key Points
Keywords: activity restriction; preterm birth; short cervix; history of preterm birth